EMDR in Cancer Patients: A Systematic Review - Portigliatti Pomeri, Alberto; La Salvia, Anna; Carletto, Sara; Oliva, Francesco; Ostacoli, Luca (Frontiers in Psychology, 2021)
Background: Psychological distress is common among patients with cancer, with severe consequences on their quality of life. Anxiety and depression are the most common clinical presentation of psychological distress in cancer patients, but in some cases cancer may represent a traumatic event resulting in posttraumatic stress disorder (PTSD). Currently, Eye Movement Desensitization and Reprocessing (EMDR) therapy is considered an evidence-based treatment for PTSD, but recent studies also showed its effectiveness for anxiety and depression. The aim of the present systematic review is to summarize the current literature on the effect of EMDR on cancer-related psychological distress. Methods: A literature search was conducted for peer-reviewed articles about “EMDR” and “cancer patients” in the following electronic databases: PubMed, MEDLINE, Science Direct, Google Scholar, and Cochrane library. Results: Our search identified 7 studies in which EMDR was used with a total of 140 cancer patients. The psychiatric diagnosis was PTSD in 3 studies. Otherwise, the diagnosis concerned the anxious and depressive disorder spectrum. Overall, EMDR treatment schedules used were highly heterogeneous, with a different number of sessions (from 2 to 12) and a different duration of therapy (up to 4 months). However, across all studies analysed EMDR therapy was judged to be adequate in reducing symptoms of psychological distress in this population. Conclusions: According to the results of our analysis, the level of evidence regarding EMDR efficacy in cancer patients is limited by the scarcity of studies and their low methodological quality. Although better quality research is needed, available data suggest that EMDR could be a promising treatment for psychological distress in patients with cancer.